Development and application of a quantitative real-time PCR method for detection of Decapod iridescent virus 1 - Zhao, Fu-Rong; Liu, Yang; Zheng, Qin; Zhang, Yan-Ge; Han, Yijuan; Zhou, Dong-Hui; Ma, Gui-Chao; Wang, Wei; Chen, Jianming (Frontiers in Microbiology, 2024)
As a newly discovered virus, Decapoda iridovirus 1 (DIV1) can cause a mortality rate of up to 100% in crustaceans, leading to huge economic losses. At present, there is no effective prevention and control measures for this disease. In the present study, the specific primers targeting highly conserved regions of MCP gene were designed, and then a quantitative real-time PCR method was established. The results indicate that DIV1 quantitative real-time PCR established has good specificity and does not cross react with other pathogens including white spot syndrome virus (WSSV), infectious subcutaneous and hematopoietic necrosis virus (IHHNV) and Vibrio parahaemolyticus induced acute hepatopancreatic necrosis disease (VpAHPND). The real-time PCR was capable of detecting DIV1 DNA at a minimum concentration of 10 copies/μL within 34 cycles. The method has good repeatability, with intra group and inter group coefficients of variation both less than 2%. Thirty-two clinical samples were assessed using both the real-time PCR and conventional PCR. The results shown real-time PCR we established are more sensitive than conventional PCR. In conclusion, this method has strong specificity, stable repeatability, and high sensitivity, providing technical support for clinical diagnosis, epidemiology investigation and monitoring of DIV1.